Analysis of stylistic and pragmatic features in literary and everyday vocabulary - Al Ahrar , Kamilla; Kendjayeva , Zemfira (The Lingua Spectrum, 2025)
The article analyzes the stylistic and pragmatic features of literary and everyday vocabulary in the Russian language. Literary and everyday vocabulary, representing different layers of speech practice, perform different functions in communication. The study examines the characteristic features of each group of vocabulary: literary vocabulary is characterized by normativity, stylistic neutrality or high style, while everyday vocabulary is manifested in informal, colloquial speech, often colored emotionally and expressively. Particular attention is paid to pragmatic aspects – the goals and attitudes of communication that influence the choice of lexical means. Examples from fiction, journalism, everyday communication and social networks are analyzed, which allows us to trace the interaction and interpenetration of these lexical levels. Cases of stylistic contrast are also considered, when everyday vocabulary is used in literary texts to create a certain effect – comic, ironic or realistic. The work demonstrates how the stylistic coloring of words and their pragmatic orientation can influence the perception of the text, as well as how the choice between literary and everyday vocabulary reflects the social, cultural and communicative features of speech.